Price transmission analysis in the Greek milk market - Ioanna Reziti (SPOUDAI - Journal of Economics and Business, 2014)
This paper examines the farm-retail price transmission mechanism in the Greek milk market by using monthly data for the period from January 1998 to June 2014. Through this period, the dairy industry underwent significant changes, resulting in increasing concentration in the market for fresh pasteurized milk. On the other hand, in the past five years, the number of dairy farms has decreased dramatically. The milk supply chain can be described as an atomized raw milk production sector confronted by a quite concentrated dairy sector. We apply an error correction model to test for asymmetric behaviour in the transmission process. The empirical results indicate that transmission between producer and consumer milk prices in Greece is asymmetric in both the short and the long run, implying that retailers exercise market power over producers.
Keywords: C10; L11; Q10; 330; asymmetric price transmission; cointegration; error correction; milk market